Communication apprehension of students in the ESL classroom / Suzilla Jamari - Jamari, Suzilla (2011)
This study attempted to investigate the communication apprehension of students in the ESL classroom. The participants consisted of 31 Bachelor of Science (Hons) Tourism Management at UiTM Melaka, who are taking BEL492 (Presentation Skills) course. Of 31 students, 9 students are male and 22 students are female. McCroskey’s (1982) Personal Report of Communication Apprehension (PRCA-24) modified version was utilized in collecting the data about communication apprehension among the students. Variables like language achievement and gender were examined. Descriptiveanalyses, Gamma-test, and independent t-test were used to find out the relationships. The findings showed that speech activity causes the highest communication apprehension among the students; followed by meeting, conversation, and group discussion activities. There were no significant influences of language achievement and gender on students’ communication apprehension. Main implications derived from this study include finding out the communication activities that cause the highest communication apprehension to work on them; and giving students more opportunities to involve in communication activities in ESL classroom to give students the familiarity with the target language. For future research, it is recommended that this topic is measured with larger group of participants, wider communication area and scope of study, and collaborate with other instruments to find out more information on students communication apprehension.